Metal remobilization and ore-fluid perturbation during episodic replacement of auriferous pyrite from an epizonal orogenic gold deposit. (15th January 2019) - Wu, Ya-Fei; Evans, Katy; Li, Jian-Wei; Fougerouse, Denis; Large, Ross R.; Guagliardo, Paul
Abstract: Mineral-scale episodic replacement of auriferous pyrite by texturally-complex pyrite, marcasite and minor arsenopyrite occurred in breccia ores from the Daqiao epizonal orogenic gold deposit, West Qinling Orogen, China. This study uses a novel combination of laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS), Nanoscale secondary ion mass spectrometry (NanoSIMS), and secondary ion mass spectrometry (SIMS) to investigate the remobilization and re-concentration of gold and other trace elements during this complex replacement process and the probable mechanism. Several lines of evidence including some degree of preservation of external morphology, sharp contacts and compositional differences between the parent pyrite and product pyrite and marcasite, and reaction-induced porosity suggest that the replacement of parent pyrite proceeds via a two-step replacement via a dissolution and reprecipitation mechanism, plus an additional marcasite overgrowth. During the replacement of euhedral pyrite, depletion of gold and other trace elements (Te, Se, Zn, Co, Tl, Ni, W, and As) in porous product pyrite relative to its precursor indicate exsolution and remobilization of these metals from crystal lattice of the original pyrite. In the subsequent replacement of porous pyrite by two types of marcasite and minor arsenopyrite, euhedral product marcasite contains low contents of trace elements, possibly due to high metal solubility in the acidic fluids favorable for marcasite precipitation. The complex-zoned marcasite significantly enriched in gold and other metals relative to porous pyrite (W, Tl, As, Sb, Ag, Se, and Zn) is thought to have formed via precipitation triggered by further oxidation and/or immediate reduction in threshold supersaturation. Dissolution of the impurity-rich pyrite and precipitation of new pyrite and marcasite generations could have occurred at low pH plus high concentrations of dissolved Fe 2+ condition caused by partial oxidation of aqueous H2 S and/or S 2− in ore fluids. The fluid oxidation is evidenced by a general decreasing trend of δ 34 S values from the parent euhedral pyrite, to product porous pyrite, euhedral marcasite, and complex-zoned marcasite. The isotopic results are consistent with ore fluid oxidation controlled by pressure fluctuations during multistage hydraulic fracturing in a fault-valve regime at Daqiao deposit. This quantitative study emphasizes that the pressure-driven hydrothermal process plays a key role in the micron- to nano-scale redistribution and re-enrichment of gold and other trace metals during episodic replacement of auriferous pyrite in brittle rheological zones from epizonal orogenic gold systems.